Les défis de la gouvernance urbaine à Manille - Yves Boquet (Bulletin de l’Association de Géographes Français)
The capital region of the Philippines is one of the largest urban areas in the world in terms of population. The official perimeter of Metro Manila (17 municipalities) is home to about 12 million people and périmetropolitan expansion brings the real figure Manila to 15 or 16 million. The rapid growth of the urban area since the 1960s has led to major management problems of housing, traffic, waste and flood risk, among others. These phenomena are interdependent. Created under Ferdinand Marcos, the National Capital Region was managed by his wife Imelda Marcos, Governor of Metro Manila. After the fall of the dictatorship, a desire for autonomy of the constituent municipalities has led to give strong powers to local governments and mayors. MMDA, the development agency of the city of Manila, which is supposed to coordinate policy development of the capital region, appears to be weak and unable to ensure harmonious growth of the city. This communication discusses some of the difficulties encountered, and examines the most relevant scale for the management of everyday life’s problems.